Influence of midwifery presence in United States centers on labor care and outcomes of low‐risk parous women: A Consortium on Safe Labor study. Issue 3 (9th November 2018) - Carlson, Nicole S.; Neal, Jeremy L.; Tilden, Ellen L.; Smith, Denise C.; Breman, Rachel B.; Lowe, Nancy K.; Dietrich, Mary S.; Phillippi, Julia C.
Abstract: Background: Sixty percent of United States births are to multiparous women. Hospital‐level policies and culture may influence intrapartum care and birth outcomes for this large population, yet have been poorly explored using a large, diverse sample. We sought to use national United States data to analyze the association between midwifery presence in maternity care teams and the birth processes and outcomes of low‐risk parous women. Methods: We conducted a retrospective cohort study using Consortium on Safe Labor data from low‐risk parous women in either interprofessional care (n = 12 125) or noninterprofessional care centers (n = 8996). Unadjusted, adjusted (age, race, health insurance type), propensity‐adjusted, and propensity‐matched logistic regression models were used to assess processes and outcomes. Results: There was concordance in outcome differences across regression models. With propensity score matching, women at interprofessional centers, compared with women at noninterprofessional centers, were 85% less likely to have labor induced (risk ratio [RR] 0.15; 95% CI 0.14‐0.17). The risk for primary cesarean birth among low‐risk parous women was 36% lower at interprofessional centers (RR 0.64; 95% CI 00.52‐0.79), whereas the likelihood of vaginal birth after cesarean for this population was 31% higher (RR 1.31; 95% CI 1.10‐1.56). There were no significant differences in neonatal outcomes. Conclusions: Parous women have significantly higher rates of vaginal birth, including vaginal birth after cesarean, and lower likelihood of labor induction when cared for in centers with midwives. Our findings are consistent with smaller analyses of midwifery practice and support integrated, team‐based models of perinatal care to improve maternal outcomes.